2017
DOI: 10.7762/cnr.2017.6.2.68
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Methods for Physical Activity and Energy Expenditure: a Review

Abstract: Physical activity is defined as any bodily movement produced by skeletal muscles that results in energy expenditure. The benefits of physical activity for health maintenance have been well documented, especially in the prevention and management of chronic diseases. Therefore, accurate measurement of physical activity and energy expenditure is essential both for epidemiological studies and in the clinical context. Given the large number of available methods, it is important to have an understanding of each, esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(108 citation statements)
references
References 85 publications
2
89
0
10
Order By: Relevance
“…Accelerometer and related wearable instruments permit collection of more objective data, as these devices do not depent on self-assessment. PA measurements vary by design and as per the individual goal for the research program (29).…”
Section: Physical Activitymentioning
confidence: 99%
“…Accelerometer and related wearable instruments permit collection of more objective data, as these devices do not depent on self-assessment. PA measurements vary by design and as per the individual goal for the research program (29).…”
Section: Physical Activitymentioning
confidence: 99%
“…It can be concluded that the average energy expenditure from playing football by using calculation was greater than pedometer. Energy expenditure from exercise is one of the components used to calculate total energy needs a day or total energy expenditure (TEE) [8]. Measuring the energy expenditure from exercise is difficult, because each individual has a different movement and the appropriate instruments are needed to be able to calculate the more appropriate energy expenditure [9].…”
Section: Resultsmentioning
confidence: 99%
“…In the determination of athlete's intake, physical energy activity measurements are used to calculate the total energy expenditure (TEE) estimates. TEE consists of three components: basal metabolic rate (BMR) or resting energy expenditure (REE), thermic effect of food (TEF), and activity energy expenditure (AEE) [8]. The measurement of physical activity during the exercise needs to be done in detail, including the frequency, intensity, and type of activity as these measurements will be taken into account in determining the AEE value and affecting the TEE value.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, some authors used accelerometry to quantify human movement while participants were using AVG (Taylor et al, 2012;Tripette et al, 2014). Accelerometers are reliable, objective, and less expensive compared to other ways of estimating energy expenditure during physical activity (Ndahimana & Kim, 2017). The output of accelerometry has been presented in counts, which are proportional to the variation of acceleration of movements (Chen, Janz, Zhu & Brychta, 2012), and in predicted metabolic equivalents of task (METs) (Cuberek, Fromel, Groffik, & Jakubec, 2017;Lyden, Kozey, Staudenmeyer, & Freedson, 2011).…”
Section: Introductionmentioning
confidence: 99%